Imaging Reactive Oxygen Species in Arthritis - Wei-Tsung Chen; Ching-Hsuan Tung; Ralph Weissleder (Molecular Imaging)
Reactive oxygen species (ROS) have been shown to play a role in the pathogenesis of arthritides. Luminol was used as the primary reporter of ROS and photons resulting from the chemiluminescence reaction were detected using a super-cooled CCD photon counting system. Luminol was injected intravenously into groups of animals with different models of arthritis. Imaging signal correlated well with the severity of arthritis in focal and pan-arthritis as determined by histological measurement of ROS by formazan. Measurements were highly reproducible, sensitive, and repeatable. In vivo chemiluminescence imaging is expected to become a useful modality to elucidate the role of ROS in the pathogenesis of arthritides and in determining therapeutic efficacy of protective therapies.